O Programa Residência Pedagógica como ação potencializadora na formação inicial de professores de Educação Física - Becker, Eriques Piccolo (2024)
The current focus on initial training (IT) for physical education teachers necessitates a thoughtful consideration of the strategies that can enrich this training process. This study aims to explore how the Pedagogical Residency Program (PRP) can contribute to enhancing the initial training of physical education teachers. The objectives of the study encompass understanding the formation process of undergraduate students in Physical Education, analyzing the role of collaborative spaces and exchange of experiences in the IT process of teachers, and evaluating the relationship between Supervised Curricular Internships (SCI) and the PRP. Employing a qualitative approach and utilizing semi-structured interviews and field diaries for data collection, based on observations of PRP Physical Education – Center: Body Culture of the Movement meetings, we aimed to construct narratives from participants. Through data triangulation and content analysis, we engaged in a critical and reflective discussion. Our findings indicate that the PRP significantly enhanced the IT of participants, particularly in terms of developing a teaching identity and fostering a sense of belonging as teachers. Moreover, it facilitated the exchange of ideas and experiences, providing future teachers with insights into the multifaceted nature of the teaching profession. However, challenges related to SCI and PRP primarily revolve around aligning the training curriculum and integrating the mandatory curricular component of SCI as the initial substantive engagement of academics within a school setting. The study underscores the significance of collaborative training spaces that bridge the gap between academia and the school environment, ensuring that IT remains contextualized and aligned with the realities of the school setting.